Decentralized Iot Edge Nanoservice Architecture for Future Gadget-Free Computing - Erkki Harjula; Pekka Karhula; Johirul Islam; Teemu Leppanen; Ahsan Manzoor; Madhusanka Liyanage; Jagmohan Chauhan; Tanesh Kumar; Ijaz Ahmad; Mika Ylianttila (IEEE Access)
In the envisioned ubiquitous world, services will follow users as they move across smart surroundings. Services are instantiated to users through the environment, appearing and disappearing as they move, which reduces the need for personal communication devices such as smartphones or tablets. To facilitate this development, service architectures need to support virtualized, on-demand service composition based on the hardware and software resources available at the current user location. The technical context for this type of user interaction with digital services through smart surroundings is called Internet of Everything (IoE). Today’s service architectures will be too inflexible in this highly decentralized and dynamic environment. Hence, in this article we propose a novel service model called nanoEdge, where nodes collaboratively provide needed functions for virtual services that need to be deployed locally due to performance, efficiency or reliability requirements, for example. The main contributions of this article are the nanoEdge conceptual model and its proof-of-concept (PoC) implementation to show that the model is feasible with regard to performance and resource-efficiency. The successful demonstration of PoC implementation exemplifies future IoE service scenarios with today’s hardware components.